Silver selenium-silver sulfur solid solution thermoelectric thin film, flexible thermoelectric thin film device and preparation method and application thereof
By introducing silver selenium-silver sulfur solid solution into inorganic thermoelectric materials and adopting multi-pass hot rolling technology, the flexibility and elastic strain of the material are improved; at the same time, by using Au and Ag as electrode materials and fixing them through screws, interface contact is reduced Resistance solves the problems of insufficient flexibility performance of thermoelectric materials and high interface contact resistance in the prior art, and achieves thermoelectric thin film devices with high power density and good flexibility.
Patent Information
- Application Number
- CN202411524894.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
The flexible properties of existing inorganic thermoelectric materials are insufficient, have high fragility, and commonly used connection designs lead to high interface contact resistance, limiting the application of flexible thermoelectric generators.
Silver selenium-silver sulfur solid solution thermoelectric film is used to introduce dislocations and refine grains through multiple passes of hot rolling to improve the elastic strain of the material; Au and Ag are used as electrode materials and fixed by screws to reduce the interface contact resistance.
It significantly improves the flexibility of the thermoelectric film, maintains good performance after 100,000 bending times, and achieves low interface contact resistivity, significantly improves the power density to about 145W/m2.
Smart Images

Figure CN119403423A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of thermoelectric materials and thermoelectric devices, and in particular to a silver-selenium-silver-sulfur solid solution thermoelectric film, a flexible thermoelectric film device, and a preparation method and application thereof. Background Art
[0002] Flexible thermoelectric generators have attracted extensive attention as self-powered batteries for wearable electronic devices. Current research focuses on developing efficient and durable flexible thermoelectric generators. Although organic thermoelectric materials such as PEDOT (polyethylene dioxythiophene), PANI (polyaniline), and PPy (polypyrrole) have become the focus of early research due to their inherent flexibility, their power factor (PF = S 2 / ρ, S is the Seebeck coefficient, ρ is the resistivity) is much lower than that of inorganic thermoelectric materials, which limits its application in thermoelectric power generation.
[0003] In recent years, bandgap engineering and carrier concentration optimization have significantly improved the power factor of inorganic thermoelectric materials, making them an ideal choice for flexible thermoelectric generators. For example, β-Ag2Se is an orthorhombic phase structure below 407K, with a bandgap of about 0.2eV and a high conductivity of 1700cm 2 / Vs carrier mobility. At 300K, the power factor of Ag2Se exceeds 20μW / cm·K 2 , the zT value reaches 0.75, showing its potential in low-temperature thermoelectric applications.
[0004] However, due to the brittle chemical bonds of inorganic materials, their flexibility is limited and fragility is a key challenge. Reducing the thickness of the material has been shown to be an effective way to improve flexibility. Therefore, researchers have prepared flexible inorganic thermoelectric films through deposition, coating, printing, and composite with organic materials. It is crucial to develop a universal and large-scale production technology for thinning bulk inorganic thermoelectric materials to prepare high-performance films. Hot rolling processes have been widely used in the production of metal films and are considered to be useful for thinning inorganic thermoelectric materials. However, the power factor of the resulting film is significantly lower than that of the bulk material due to its low density, high defect concentration, and low crystal quality.
[0005] In practical applications, flexible thermoelectric generators can only be bent a limited number of times, usually less than 2,000 times. Ensuring elastic properties is key to maintaining the durability of device functions. Currently, there is little research on the elastic properties of thermoelectric materials. Due to the fragile chemical bonds of inorganic materials, they usually exhibit a small maximum elastic strain.
[0006] In addition, the electrode and material connection design in common flexible devices usually uses cumbersome and energy-consuming evaporation technology or silver paste with poor wettability. Both methods have high contact resistance for the material / electrode interface, which makes the overall output efficiency of the device far lower than the theoretical prediction.
[0007] Chinese patent CN 117998962 A discloses a flexible silver selenide thin film thermoelectric device with high power density, a preparation method and an application thereof, wherein the flexible silver selenide thin film thermoelectric device is composed of a plurality of n-type silver selenide thin film legs connected in series by copper wires, and the structure of the n-type silver selenide thin film legs is Ag / Au / Ag2Se, wherein Ag2Se is an Ag2Se thin film layer, and Au and Ag are electrode layers. The silver selenide thin film prepared by the invention has both excellent flexibility and thermoelectric performance, but the Ag2Se thin film layer can only be bent under the condition of a curvature radius of 3mm when the thickness is about 36 microns, and its flexibility still needs to be improved. Summary of the invention
[0008] The purpose of the present invention is to provide a silver-selenium-silver-sulfur solid solution thermoelectric film, a flexible thermoelectric film device and a preparation method and application thereof, so as to improve the flexibility of the thermoelectric film.
[0009] The purpose of the present invention can be achieved by the following technical solutions:
[0010] On the one hand, the present invention provides a silver-selenium-silver-sulfur solid solution thermoelectric film, wherein the silver-selenium-silver-sulfur solid solution thermoelectric film is an n-type silver-selenium-silver-sulfur solid solution thermoelectric film, and the structure is Ag / Au / Ag2Se 1-x S x , 0.05≤x≤0.3, where Ag2Se 1-x S x It is the active layer of the thermoelectric thin film, and Ag and Au are the electrode layers.
[0011] Preferably, the Ag electrode layer has a thickness of 0.15 to 0.25 mm, a width of 2 to 3 mm, and a length of 4 to 6 mm.
[0012] Preferably, the Au electrode layer has a thickness of 60 to 90 nm, a width of 2 to 3 mm, and a length of 4 to 6 mm.
[0013] Preferably, the Ag2Se 1-x S x The active layer of the thermoelectric film has a thickness of 25 to 70 μm, a width of 4 to 6 mm, and a length of 18 to 22 mm.
[0014] In a second aspect, the present invention also provides a method for preparing the above-mentioned silver-selenium-silver-sulfur solid solution thermoelectric thin film, comprising the following steps:
[0015] S1, according to Ag2Se 1-x S x The single-element raw materials Ag, Se and S are weighed in a stoichiometric ratio, mixed and then vacuum packaged;
[0016] S2, heating the Ag, Se and S that were vacuum-encapsulated after mixing in step S1 until they are in a molten state and fully react to obtain a molten material;
[0017] S3, cooling the melt obtained in step S2 to room temperature to form a silver selenium-silver sulfur solid solution ingot, and obtaining Ag2Se by cutting, rolling and cutting. 1-x S x Thermoelectric thin film active layer;
[0018] S4, in Ag2Se 1-x S x The surface of the active layer of the thermoelectric film is sprayed with gold, and then a silver foil is arranged on the side sprayed with gold to form the silver-selenium-silver-sulfur solid solution thermoelectric film.
[0019] Preferably, in step S1, the purity of the single-substance raw materials Ag, Se and S is greater than 99.99%.
[0020] Preferably, in step S2, the heating process conditions are: heating from room temperature to 950-1150° C. at a heating rate of 90-130° C. per hour, and keeping the temperature for 6-10 hours.
[0021] Preferably, in step S3, the cooling process condition is: cooling to room temperature at a cooling rate of 120-180° C. per hour.
[0022] Preferably, in step S3, the cutting process conditions are: cutting the silver-selenium-silver-sulfur solid solution ingot into thin slices with a thickness of 1.8 to 2.2 mm by wire cutting.
[0023] Preferably, in step S3, the rolling process conditions are: rolling the sheet into a film with a thickness of 25 to 70 μm at a speed of 50 to 70 mm / s at a temperature of 100 to 140°C.
[0024] The present invention introduces dislocations and refines grains through multiple hot rolling passes, thereby increasing the elastic strain of the material and enhancing the elastic bending performance.
[0025] Preferably, in step S3, the cutting process conditions are: cutting the film into Ag2Se with a length of 18 to 22 mm and a width of 4 to 6 mm. 1-x S x Thermoelectric thin film active layer.
[0026] In a third aspect, the present invention further provides a flexible thermoelectric thin film device, comprising the above-mentioned silver-selenium-silver-sulfur solid solution thermoelectric thin film.
[0027] Preferably, the silver-selenium-silver-sulfur solid solution thermoelectric film is used as a silver-selenium-silver-sulfur solid solution thermoelectric film leg, and the silver-selenium-silver-sulfur solid solution thermoelectric film leg has a thickness of 175 to 320 μm, a width of 4 to 6 mm, and a length of 18 to 22 mm.
[0028] Preferably, the flexible thermoelectric thin film device is composed of copper wires connecting the silver-selenium-silver-sulfur solid solution thermoelectric thin film legs in series, and the number of the silver-selenium-silver-sulfur solid solution thermoelectric thin film legs is 4 to 8.
[0029] Further preferably, the number of the silver-selenium-silver-sulfur solid solution thermoelectric thin film legs is 6.
[0030] Preferably, the preparation is carried out by the following steps: passing a copper wire through the Ag electrode layer, the Au electrode layer and the Ag2Se electrode layer of the legs of the silver-selenium-silver-sulfur solid solution thermoelectric film in sequence. 1-x S x The thermoelectric film active layer is formed, and the legs of the silver-selenium-silver-sulfur solid solution thermoelectric film are connected in series to obtain the flexible thermoelectric film device.
[0031] Preferably, before connecting the legs of the silver-selenium-silver-sulfur solid solution thermoelectric film in series with copper wire, the Au electrode layer and the Ag electrode layer need to be connected to the Ag2Se 1-x S x The active layer of the thermoelectric film is fixed. In the present invention, Ag and Au with ohmic contact fixed by screws are used as electrodes, so that a high-power density flexible thermoelectric film device with extremely low interface contact resistivity can be obtained.
[0032] In a fourth aspect, the present invention also provides an application of the above-mentioned flexible thermoelectric thin film device, wherein the flexible thermoelectric thin film device is used to prepare a wearable device.
[0033] The present invention obtains Ag2Se by alloying Ag2Se with Ag2S. 1-x S x alloys, the crystal structure can transform from orthorhombic phase to monoclinic phase, and the alloys with x>0.3 show high ductility due to their wrinkled layer structure and weak Ag-S chemical bonds. 1-x S x (x>0.3) The power factor of alloy films is low, usually less than 10μW / cm-K 2 ; However, alloy films with 0.05≤x≤0.3 can retain the thermoelectric properties of the bulk material.
[0034] The silver selenium-silver sulfur solid solution (Ag2Se 1-xS x , 0.05≤x≤0.3), has excellent thermoelectric properties at room temperature, shows a high Seebeck coefficient and low thermal conductivity, and has become one of the current high-performance thermoelectric materials at room temperature. In addition, the silver selenium-silver sulfur solid solution also has excellent plasticity that other common inorganic thermoelectric materials do not have. This material property provides feasibility for the present invention to realize the preparation of self-supporting silver selenium-silver sulfur solid solution thermoelectric film and apply it to flexible thermoelectric devices. On the other hand, by using Au and Ag as electrode materials and fixing the electrodes and the film with screws, the interface contact resistance is significantly reduced, and the interface resistivity of the prepared thermoelectric film legs is as low as ~6.8mΩ·cm 2 , which is much lower than the contact resistivity of existing flexible thermoelectric thin film devices, thus achieving high power output of the device. With excellent film material properties and optimized electrode structure, the six-legged silver selenium-silver sulfur solid solution flexible thermoelectric thin film device of the present invention can achieve a power density of about 145W / m when the temperature difference is 76K. 2 In addition, Ag2Se 1-x S x The micrometer-level thickness of the thermoelectric film active layer gives it a certain degree of mechanical flexibility. 1-x S x The thermoelectric film can be bent 100,000 times around the little finger of an adult (bending radius of 3 mm), and the device performance remains stable. The silver-selenium-silver-sulfur solid solution thermoelectric film and its thermoelectric device of the present invention have achieved significant technical breakthroughs in both mechanical flexibility and power output, demonstrating the huge application potential of inorganic materials in the field of flexible thermoelectric devices, and can be widely used in wearable devices and other fields in the future.
[0035] Existing flexible thermoelectric devices mainly use all-organic materials, organic / inorganic composite materials, and inorganic flexible thermoelectric materials with substrates. Although conductive polymers and carbon-based materials show good flexibility, their thermoelectric properties are still not comparable to those of inorganic thermoelectric materials. Although inorganic thermoelectric films prepared by chemical vapor deposition, spin coating and other methods are flexible, their thermoelectric properties are not as good as the corresponding bulk materials due to problems such as high impurity concentration, many defects, low crystallinity and insufficient density, which directly affects the output power of the device. The present invention uses silver selenium-silver sulfur solid solution materials with high thermoelectric properties at room temperature to prepare thin film thermoelectric materials, and the power factor can reach about 17μW·cm-1K-2. At the same time, a self-supporting Ag2Se with excellent bending flexibility is prepared by medium-temperature rolling. 1-x S x The thermoelectric film can maintain good performance after being bent 100,000 times under the condition of a curvature radius of 3 mm. Therefore, the silver-selenium-silver-sulfur solid solution film prepared by the present invention has both excellent flexibility and thermoelectric performance.
[0036] In existing flexible devices, the connection between electrodes and materials usually adopts cumbersome and energy-consuming evaporation technology or silver paste with poor wettability, resulting in high contact resistance. The present invention uses silver and gold as electrode materials and fixes them by screws, so that ohmic contact is formed between the electrodes, and the contact between the electrodes and the materials is extremely close. As a result, the silver-selenium-silver-sulfur solid solution thin film thermoelectric device prepared by the present invention achieves low interface contact resistivity and significantly improves the power density. In addition, this connection method has good universality. The silver-selenium-silver-sulfur solid solution thin film thermoelectric device of the present invention not only retains the excellent thermoelectric properties of inorganic thermoelectric materials, but also overcomes its inherent rigidity, showing great potential in the application of flexible thermoelectric devices.
[0037] Compared with the prior art, the present invention adjusts the ratio of selenium to sulfur in the silver-selenium-silver-sulfur solid solution (Ag2Se 1-x S x , 0.05≤x≤0.3), developed a series of recoverable flexible Ag2Se with wide thickness range (25~70 μm) selectivity 1-x S x Thermoelectric film. The prepared films can be bent under the condition of a curvature radius of 3 mm. In addition, the film of the present invention not only exhibits excellent thermoelectric performance comparable to the Ag2Se film disclosed in the prior art, but also, due to the influence of the phase transition temperature of the material, the assembled thin film device can be selectively applied according to different temperature regions.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The silver selenium-silver sulfur solid solution thermoelectric film prepared by the present invention has excellent flexibility and thermoelectric properties. The prepared flexible thermoelectric device is significantly superior to most existing flexible thermoelectric devices in terms of power density and flexibility.
[0040] (2) Ag2Se prepared by the present invention 1-x S x The thermoelectric film can still maintain good performance after being bent 100,000 times with a curvature radius of 3mm.
[0041] (3) Ag2Se prepared by the rolling process of the present invention 1-x S x Thermoelectric thin film, and can maintain thermoelectric properties comparable to bulk materials, Seebeck coefficient, Hall mobility and power factor are comparable to bulk materials. Compared with most silver-selenium-based thin films, silver-selenium-silver-sulfur solid solution thermoelectric thin film shows greater advantages.
[0042] (4) Ag2Se prepared by the present invention 1-x Sx The thermoelectric film is a diverse and recoverable flexible thermoelectric film with a wide range of thickness selectivity. By adjusting the sulfur and selenium content in the silver selenium-silver sulfur solid solution, recoverable bending performance can be obtained at a thicker size. With the increase of sulfur content, Ag2Se 1-x S x The thermoelectric film can still achieve a bending of about 3mm at a maximum thickness of 68μm.
[0043] (5) The flexible thermoelectric device prepared by the present invention has a variety of selectivities in its working range. By adjusting the sulfur and selenium contents in the silver-selenium-silver-sulfur solid solution, the present invention obtains a variety of flexible thermoelectric devices that can be used and selected in different temperature zones.
[0044] (6) The present invention uses silver and gold as electrode materials and fixes them by screws, so that ohmic contact is formed between the electrodes. At the same time, the contact between the electrode and the material is extremely close. Therefore, the silver selenium-silver sulfur solid solution thin film thermoelectric device prepared by the present invention achieves low interface contact resistivity and significantly improves the power density. When the temperature difference is 76K, the power density can reach about 145W / m 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 The XRD diffraction patterns of the silver-selenium-silver-sulfur solid solution block (a) and the film (b) of the present invention;
[0046] Figure 2 The lowest softening temperature of silver selenium-silver sulfur solid solution (a), the size change photo of silver selenium-silver sulfur solid solution after multiple hot rolling (b), Ag2Se 1-x S x The maximum thickness of the thermoelectric film that can be bent at a radius of about 3 mm (c), and the compressive stress-strain curves of hot-rolled and unhot-rolled silver-selenium-silver-sulfur solid solution bulk materials (d);
[0047] Figure 3 It is a bulk of silver selenium-silver sulfur solid solution and Ag2Se at room temperature. 1-x S x Seebeck coefficient (a), Hall mobility (μ H )(b) and power factor (PF)(c) and Hall carrier concentration (n H ) and a comparison chart with data in the literature;
[0048] Figure 4 The resistance change of silver selenium-silver sulfur solid solution thermoelectric film when the bending radius is 3mm (R / R avg. )(a), Seebeck coefficient change (S / S avg. )(b) Power factor change (PF / PF avg.)(c) and the interfacial contact resistivity of the thermoelectric film legs and the comparison with the values reported in the literature (d);
[0049] Figure 5 Figure 2 shows the relationship between the load voltage (V), output power (P) and loop current (I) of the 6-legged silver selenium-silver sulfur solid solution thermoelectric thin film device under different temperature differences (a), the maximum output power (P max )(b), Maximum output power density (P d max )(c) Relationship with temperature difference and comparison of normalized output power density of devices (d). DETAILED DESCRIPTION
[0050] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0051] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0052] The open circuit voltage (V oc ), maximum output power density (P d max ), internal resistance (R in ), interface contact resistivity (R contact ) etc. can be obtained by conventional measurement methods in this field.
[0053] (A) A silver selenium-silver sulfur solid solution thermoelectric film (Ag / Au / Ag2Se 1-x S x , 0.05≤x≤0.3)
[0054] Example 1: x = 0.05
[0055] (1) Raw material preparation: Select single element Ag, Se, S with purity greater than 99.99%, according to Ag2Se 0.95 S 0.05 The stoichiometric ratio is weighed and vacuum sealed in a quartz tube.
[0056] (2) High-temperature smelting: The quartz tube containing the raw materials is suspended in a high-temperature smelting furnace, and the temperature of the tip of the quartz tube is increased from room temperature to 1050°C at a rate of 110°C per hour and maintained for 8 hours to ensure that the raw materials are fully reacted in a molten state.
[0057] (3) Cooling and solidification: The high-temperature melt obtained in step (2) is cooled, and the temperature of the quartz tube tip is reduced to room temperature at a rate of about 150° C. per hour, and the silver-selenium-silver-sulfur solid solution ingot is taken out.
[0058] (4) Thin film preparation: The silver selenium-silver sulfur solid solution ingot obtained in step (3) was cut into a plurality of thin sheets with a thickness of about 2 mm using a wire cutting machine, and then repeatedly rolled at a rolling rate of 60 mm / s at 120° C. to obtain Ag2Se films with a thickness of about 29 μm to 68 μm. 1-x S x Thermoelectric film. Finally, the film was cut into a size of 20 mm × 5 mm (length × width).
[0059] (5) Electrode assembly: Using a scanning electron microscope (SEM) to spray gold on Ag2Se 1-x S x The opposite ends of the thermoelectric film legs are sprayed with a 5mm×2.5mm×78nm (length×width×thickness) Au layer, and a hand-twisted drill is used to punch small circular holes with a radius of 1mm at both ends of the gold-sprayed film. 1-x S x Thermoelectric film composition Ag / Au / Ag2Se 1-x S x The film legs are fixed with screws to obtain the silver-selenium-silver-sulfur solid solution thermoelectric film.
[0060] Example 2: x = 0.1
[0061] Select the single element Ag, Se, S with purity greater than 99.99%, and press Ag2Se 0.9 S 0.1 The chemical stoichiometric ratio is weighed and vacuum-sealed in a quartz tube, and the rest is the same as in Example 1.
[0062] Example 3: x = 0.15
[0063] Select the single element Ag, Se, S with purity greater than 99.99%, and press Ag2Se 0.85 S 0.15 The chemical stoichiometric ratio is weighed and vacuum-sealed in a quartz tube, and the rest is the same as in Example 1.
[0064] Example 4: x = 0.2
[0065] Select the single element Ag, Se, S with purity greater than 99.99%, and press Ag2Se 0.8 S 0.2 The chemical stoichiometric ratio is weighed and vacuum-sealed in a quartz tube, and the rest is the same as in Example 1.
[0066] Example 5: x = 0.25
[0067] Select the single element Ag, Se, S with purity greater than 99.99%, and press Ag2Se 0.75 S 0.25 The chemical stoichiometric ratio is weighed and vacuum-sealed in a quartz tube, and the rest is the same as in Example 1.
[0068] Example 6: x=0.3
[0069] Select the single element Ag, Se, S with purity greater than 99.99%, and press Ag2Se 0.7 S 0.3 The chemical stoichiometric ratio is weighed and vacuum-sealed in a quartz tube, and the rest is the same as in Example 1.
[0070] The Ag2Se prepared in Examples 1 to 6 1-x S x Thermoelectric film was tested for performance, and the results are as follows:
[0071] Figure 1 The silver selenium-silver sulfur solid solution block (a) and Ag2Se prepared in Examples 1 to 6 are shown. 1-x S x X-ray diffraction (XRD) pattern of thermoelectric film (b). XRD analysis results show that Ag2Se prepared by the medium temperature rolling method of the present invention 1- x S x Compared with bulk materials, thermoelectric films have certain orientation, especially in the (013) direction.
[0072] Figure 2 The lowest softening temperature of the silver selenium-silver sulfur solid solution prepared in Examples 1 to 6 (a), the dimensional change after multiple hot rolling (b), and the Ag2Se 1-x S x The maximum thickness of the thermoelectric film that can be bent at a curvature radius of about 3 mm (c), and the compressive stress-strain curves of hot-rolled and unhot-rolled silver-selenium-silver-sulfur solid solution bulk materials (d). Figure 2 (a) It can be seen that the minimum softening temperature of the silver-selenium-silver-sulfur solid solution decreases with the increase of sulfur content; Figure 2 (b) shows that the silver selenium-silver sulfur solid solution can be easily deformed and rolled into a thin film; Figure 2 (c) shows that with the increase of sulfur content, Ag2Se 1-x S x Thermoelectric films can still achieve a bend of about 3 mm at a greater thickness; Figure 2 (d) shows that after hot rolling, Ag2Se 1-x Sx The yield strength of the thermoelectric film is significantly improved, which is beneficial to the recoverable bending performance of the film.
[0073] Figure 3 The silver selenium-silver sulfur solid solution blocks and Ag2Se prepared in Examples 1 to 6 are shown. 1-x S x The Seebeck coefficient (S,a) and Hall mobility (μ) of thermoelectric films at room temperature H ,b) and power factor (PF,c) and Hall carrier concentration (n H These data show that the Ag2Se prepared by the present invention 1-x S x The thermoelectric performance of thermoelectric films is basically equivalent to that of bulk materials. Specifically, the Seebeck coefficient ( Figure 3 a) At higher temperatures, it is slightly reduced compared to bulk materials, but the reduction is small; the Hall mobility ( Figure 3 b) slightly lower than that of the bulk material, mainly due to the increase in dislocation density; the power factor ( Figure 3 c) is basically comparable to bulk materials at the same temperature. Compared with most silver selenium-based films, Ag2Se 1-x S x Thermoelectric thin films show greater advantages and lay the foundation for achieving high power output.
[0074] Figure 4 The silver selenium-silver sulfur solid solution thermoelectric film (Ag / Au / Ag2Se 1-x S x ) Resistance after 100,000 bends at a bending radius of 3 mm (R / R avg. ,a), Seebeck coefficient (S / S avg. ,b) and power factor (PF / PF avg. , c) have no obvious changes, proving its excellent flexibility. Through the four-probe method test, the interface contact resistivity of the silver selenium-silver sulfur solid solution thermoelectric film legs prepared in Examples 1 to 6 of the present invention is about 6.8 mΩ·cm 2 ( Figure 4 d). Compared with the contact resistance of the thermoelectric legs of typical thermoelectric thin film elements in the literature, the interface contact method adopted by the present invention has the lowest interface resistivity, thereby effectively reducing the negative impact of the interface resistance on the output power of the device.
[0075] (II) Preparation of a flexible silver-selenium-silver-sulfur solid solution thermoelectric thin film device
[0076] Example 7
[0077] The silver-selenium-silver-sulfur solid solution thermoelectric film prepared in Example 2 was used as a film leg, and six silver-selenium-silver-sulfur solid solution thermoelectric film legs were connected in series with copper wires in sequence to assemble a flexible silver-selenium-silver-sulfur solid solution thermoelectric film device.
[0078] Example 8
[0079] The silver-selenium-silver-sulfur solid solution thermoelectric film prepared in Example 4 was used as a film leg, and six silver-selenium-silver-sulfur solid solution thermoelectric film legs were connected in series with copper wires in sequence to assemble a flexible silver-selenium-silver-sulfur solid solution thermoelectric film device.
[0080] Example 9
[0081] The silver-selenium-silver-sulfur solid solution thermoelectric film prepared in Example 6 was used as a film leg, and six silver-selenium-silver-sulfur solid solution thermoelectric film legs were connected in series with copper wires in sequence to assemble a flexible silver-selenium-silver-sulfur solid solution thermoelectric film device.
[0082] The performance of the six-legged silver selenium-silver sulfur solid solution thin film devices prepared in Examples 7 to 9 was systematically tested. The results are as follows: Figure 5 shown. Figure 5 a shows that there is a clear relationship between the load voltage (V) and the loop current (I) of the six-legged silver selenium-silver sulfur solid solution thin film device of the present invention. As the loop current increases, the load voltage gradually decreases. This phenomenon is mainly attributed to the fact that under the condition of a fixed temperature difference, the increase in the loop current causes the resistance value of the load resistor to decrease, thereby causing a decrease in the load voltage; at the same time, the voltage value will increase accordingly with the increase in the temperature difference. Unlike the change in load voltage, the output power (P) shows a characteristic of first increasing and then decreasing with the increase in the loop current, and usually reaches a peak value when the load resistance is equal to the internal resistance of the module. At the same time, the greater the temperature difference, the greater the output power. Figure 5 b, c show the maximum output power density (P max ) and maximum power density (P d max ) changes with temperature difference, and the comparison diagram of the normalized output power density of the device ( Figure 5 d) When the temperature difference is 76K, the maximum output power density of the thin film thermoelectric device is about 145W / m 2 , which is significantly higher than most thin-film thermoelectric devices reported in the existing literature. In addition, the normalized output power density of the device reaches about 5μW / cm-K 2 , indicating that the silver-selenium-silver-sulfur solid solution thin film device of the present invention exhibits outstanding superiority in output performance.
[0083] In summary, the present invention is excellent in device bending flexibility and output power, and has great potential for application in wearable devices.
[0084] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A silver-selenium-silver-sulfur solid solution thermoelectric thin film, characterized in that: The silver selenium-silver sulfur solid solution thermoelectric film is an n-type silver selenium-silver sulfur solid solution thermoelectric film, and the structure is Ag / Au / Ag2Se 1-x S x , 0.05≤x≤0.3, where Ag2Se 1-x S x It is the active layer of the thermoelectric thin film, and Ag and Au are the electrode layers.
2. The silver-selenium-silver-sulfur solid solution thermoelectric thin film according to claim 1, characterized in that: The thickness of the Ag electrode layer is 0.15-0.25 mm, the width is 2-3 mm, and the length is 4-6 mm; the thickness of the Au electrode layer is 60-90 nm, the width is 2-3 mm, and the length is 4-6 mm; the Ag2Se 1-x S x The active layer of the thermoelectric film has a thickness of 25 to 70 μm, a width of 4 to 6 mm, and a length of 18 to 22 mm.
3. The method for preparing a silver-selenium-silver-sulfur solid solution thermoelectric thin film according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, according to Ag2Se 1-x S x The single-element raw materials Ag, Se and S are weighed in a stoichiometric ratio, mixed and then vacuum packaged; S2, heating the Ag, Se and S that were vacuum-encapsulated after mixing in step S1 until they are in a molten state and fully react to obtain a molten material; S3, cooling the melt obtained in step S2 to room temperature to form a silver selenium-silver sulfur solid solution ingot, and obtaining Ag2Se by cutting, rolling and cutting. 1-x S x Thermoelectric thin film active layer; S4, in Ag2Se 1-x S x The surface of the active layer of the thermoelectric film is sprayed with gold, and then a silver foil is arranged on the side sprayed with gold to form the silver-selenium-silver-sulfur solid solution thermoelectric film.
4. The method for preparing a silver-selenium-silver-sulfur solid solution thermoelectric thin film according to claim 3, characterized in that: In step S2, the heating process conditions are: heating from room temperature to 950-1150°C at a heating rate of 90-130°C per hour, and keeping the temperature for 6-10 hours.
5. The method for preparing a silver-selenium-silver-sulfur solid solution thermoelectric thin film according to claim 3, characterized in that: In step S3, The cooling process conditions are: cooling to room temperature at a cooling rate of 120-180°C per hour; The cutting process conditions are as follows: cutting the silver-selenium-silver-sulfur solid solution ingot into thin slices with a thickness of 1.8 to 2.2 mm by wire cutting; The rolling process conditions are: rolling the sheet into a film with a thickness of 25 to 70 μm at a speed of 50 to 70 mm / s at a temperature of 100 to 140° C.; The cutting process conditions are as follows: the film is cut into Ag2Se sheets with a length of 18 to 22 mm and a width of 4 to 6 mm. 1- x S x Thermoelectric thin film active layer.
6. A flexible thermoelectric thin film device, characterized in that: It comprises the silver-selenium-silver-sulfur solid solution thermoelectric film as described in any one of claims 1 to 2.
7. The flexible thermoelectric thin film device according to claim 6, characterized in that: The silver-selenium-silver-sulfur solid solution thermoelectric film is used as a silver-selenium-silver-sulfur solid solution thermoelectric film leg, and the silver-selenium-silver-sulfur solid solution thermoelectric film leg has a thickness of 175-320 μm, a width of 4-6 mm, and a length of 18-22 mm.
8. The flexible thermoelectric thin film device according to claim 7, characterized in that: The flexible thermoelectric film device is composed of copper wires serially connecting the legs of the silver-selenium-silver-sulfur solid solution thermoelectric film, and the number of the legs of the silver-selenium-silver-sulfur solid solution thermoelectric film is 4 to 8.
9. The method for preparing a flexible thermoelectric thin film device according to claim 8, characterized in that: The preparation is carried out by the following steps: a copper wire is passed through the Ag electrode layer, the Au electrode layer and the Ag2Se electrode layer of the legs of the silver selenium-silver sulfur solid solution thermoelectric film in sequence. 1-x S x The thermoelectric film active layer is formed, and the legs of the silver-selenium-silver-sulfur solid solution thermoelectric film are connected in series to obtain the flexible thermoelectric film device.
10. An application of the flexible thermoelectric thin film device according to claim 6, characterized in that: The flexible thermoelectric thin film device is used for preparing wearable equipment.
Citation Information
Patent Citations
Silver selenide thermoelectric composite film and preparation method and application thereof
CN114226210A
Method for preparing ultra-flexible high-performance sulfur-doped silver selenide / nylon composite thermoelectric thin film
CN114388686A
Flexible silver selenide thin film thermoelectric device with high power density and preparation method and application thereof
CN117998962A